TRANSLATION AND CROSS-CULTURAL ADAPTATION OF GENERIC SKILL SELF-ASSESSMENT INSTRUMENT FOR INDONESIAN UNDERGRADUATE MEDICAL STUDENTS - Puspadewi, Natalia; Anastasia, Gisella; Rukmini, Elisabeth (Universitas Gadjah Mada, 2023)
Background: There are various educational strategies that promote generic skills development in medical education; hence, there is a need for a valid and reliable instrument to assess them. This study aims to translate and adapt a generic skills self-assessment instrument developed by Groen et al.1 to assess Indonesian medical student’s generic skills in a classroom context.Methods: WHO's guidelines were used for the translation process, which consisted of: 1) forward translation, 2) expert panel review (using the Delphi method), 3) back translation, 4) pre-testing and cognitive interviews, and 5) the final version. Additional measures were employed to improve the translation accuracy, including proofreading (prior to step 2), expert panel review after step 3 and 4, and pilot testing along with psychometric testing after step 5. Backward translation was done by a professional translation service. Ten fourth-year students from Atma Jaya School of Medicine and Health Sciences were involved in step 4; meanwhile, we piloted the translated instrument to 35 other fourth-year students from the same sample pool. We also conducted an internal reliability test using Cronbach's alpha and construct validity test, including corrected total-item correlation and principal component analysis.Results: Steps 1-3 produced an Indonesian version of the generic skills assessment instrument with good face and content validity. Quantitative data analysis showed high internal reliability (Cronbach’s Alpha = .955) and acceptable item-total correlation (ranging from .345 to .757).Conclusion: Factor analysis showed 6 domains labelled as analytical skills, teamwork, communication skills, perseverance, social judgment, and global abstraction skills.